Proton-beam engineered surface-point defects for highly sensitive and reliable NO2 sensing under humid environments - Bang, Jae Hoon; Kwon, Yong Jung; Lee, Jung-Hoon; Mirzaei, Ali; Lee, Ha Young; Choi, Hyeunseok; Kim, Sang Sub; Jeong, Young Kyu; Kim, Hyoun Woo (ELSEVIER, 2021)
Cross-interference with humidity is a major limiting factor for the accurate detection of target gases in semiconductor metal-oxide gas sensors. Under humid conditions, the surface-active sites of metal oxides for gas adsorption are easily deactivated by atmospheric water molecules. Thus, development of a new approach that can simultaneously improve the two inversely related features for realizing practical gas sensors is necessary. This paper presents a facile method to engineer surface-point defects based on proton-beam irradiation. The sensor irradiated with a proton beam shows not only an improved NO2 response but also considerable tolerance toward humidity. Based on surface analyses and DFT calculations, it is found that proton beams induce three types of point defects, which make NO2 molecules preferentially adsorb on the ZnO surfaces compared to H2O molecules, eventually enabling improved NO2 detection with less humidity interference.
Keywords: ZNO NANORODS; GAS SENSOR; OXYGEN; VACANCIES; NANOCOMPOSITES; IRRADIATION; ABSORPTION; NANOWIRE